Akulturasi Islam Dan Budaya Jawa pada Ruang Liwan Masjid Gedhe Mataram Kotagede - Pradianti Lexa Savitri; B. Sumardiyanto (Universitas Sebelas Maret Surakarta, 2021)
This article aims to demonstrate the acculturation of Islam and Javanese culture in the Liwan Room of “Gedhe Mataram” Mosque, Kotagede. Islamic and Javanese culture’s acculturation in the building, especially mosque, important known to add insight about the tolerance between two cultural elements that can occur in the architecture’s world. Liwan room is part of the space of a mosque which functions as a prayer area. Liwan Room at the “Gedhe Mataram” Mosque, Kotagede has a distinctive design considering this mosque is the first and oldest mosque in Yogyakarta. The development of Islam in Java, especially in Yogyakarta, resulted in the transformation of local civilizations. Islam and Javanese culture itself are two different elements and have their own value. The entry of Islamic culture to Java had an impact on the acculturation of Islam and Javanese culture, where Javanese culture had already lived during the time of the Javanese Hindu kingdoms. The method used is a qualitative research method with a philosophical approach supported by observation and library studies. As a result, there is an acculturation of Islam and Javanese culture in the Liwan Room of “Gedhe Mataram” Mosque, Kotagede in layout, interior elements and ornaments in the Liwan room.